Strategic gender research contributes to policy change in North and Sub-Saharan Africa and South Asia with potential livelihood improvements for smallholder farmers in those regions. - CGIAR Research Program on Wheat (2021)
MAIZE and WHEAT researchers, together with colleagues from within and outside the CGIAR, contributed to two important policy impacts and practices (Morocco) and published findings with clear policy implications (3 countries in S. Asia, Ethiopia, Malawi, Tanzania), based on gender-transformative research and methods. Researchers are also able to influence policy change with potentially longer-term social change impacts (Nepal, Zambia). From a CGIAR-internal perspective, researchers expanded the reach of gender-transformative research.